Bridging known and new: Inquiry and intersubjectivity in parent-child interactions. (June 2019) - Vandermaas-Peeler, Maureen; Westerberg, Lauren; Fleishman, Hailey
Abstract: Sociocultural analyses of children's learning encompass their complex interactions with adults and others during joint participation in everyday activities. The study aim was to analyze the relationship between inquiry, intersubjectivity, and bridges. Intersubjectivity is a process of meaning-making through collaboration and communication. Parents reference shared experiences with young children in order to connect or "bridge" known and new information. Through a case study analysis of four families' interactions in two games performed together at home, we addressed the question, "How do parents and children co-construct meaning and knowledge during joint participation in challenging activities?" Findings revealed that parents used bridges as cognitive strategies to support young children's complex inquiry processes such as comparing and predicting. Through bridging, parents and children co-created knowledge within the child's zone of proximal development. Bridging fostered intersubjectivity by establishing a mutual focus of attention, shared emotions, and connections to a larger community of family and friends. The case study results highlight the importance of studying collaborative interactions to understand how meaning-making and knowledge construction occur during children's participation in everyday activities with parents.